Privatisation of squatters resettlement - Jamaluddin, Zakiyah (Universiti Utara Malaysia, 2005)
The issue of squatters has been the focus of much attention from the government and the media in Malaysia. This is often related to the problems of low cost housing viz, housing inadequacy, inability to buy a low cost house by the squatters and competition with the middle class income group. Therefore, delay in processing and approval of land development, high cost of construction, lack of organisational and functional coordination among various governments housing corporations – federal, regional, state and local, also cause the various problems in the construction of low cost housing.The Malaysian government has imposed the construction of low cost housing to alleviate squatters, especially by the public sector. However, constraint of budget and economic depression have brought up the role of private sector in providing enough low cost houses. One of the programmes that has been implemented is privatization of squatter’s resettlement, which is under the Special Low Cost Housing Programme that has been launched since 1985.